Nutritional Management and Recommendation for Preterm Infants: A Narrative Review - Rinawati Rohsiswatmo (Amerta Nutrition, 2021)
Background: Preterm birth is defined as birth before 37 completed weeks of pregnancy. It is the most important predictor of adverse health and development infant outcomes that extend into the early childhood and beyond. It is also the leading cause of childhood mortality under 5 years of age worldwide and responsible for approximately one million neonatal deaths. It is also a significant contributor to childhood morbidities, with many survivors are facing an increased risk of lifelong disability and poor quality of life. Purpose: In this article, we aimed to describe features of preterm infants, what makes them different from term infants, and what to consider in nutritional management of preterm infants through a traditional narrative literature review. Discussion: Preterm infants are predisposed to more health complications than term infants with higher morbidity and mortality. This morbidity and mortality can be reduced through timely interventions for the mother and the preterm infant. Maternal interventions, such as health education and administration of micronutrient supplementation, are given before or during pregnancy and at delivery, whereas appropriate care for the preterm infants should be initiated immediately after birth, which include early breastfeeding and optimalization of weight gain. Conclusion: Essential care of the preterm infants and early aggressive nutrition should be provided to support rapid growth that is associated with improved neurodevelopmental outcomes. The goal is not only about survival but making sure that these preterm infants grow and develop without any residual morbidity.